Pemberdayaan Jiwa Enterpreneur Santri Melalui Produksi Snack ABCD Di PPTQ Al Hadi Imaan Dukun Gresik - Anisatun Nur Laili; Erni Wulandari; Anny Mahmudah; Moch Hanna Wijaya Saputra; Moh Ari Novan Susanto; Khoirur Rudi; Eliyatin Mahmudah (KERIS : Journal of Community Engagement, 2021)
The challenges of the global economy, especially in Asia, have been enough to invite a response from several actors, especially in the field of Islamic scientist but also become entrepreneurs who are able to survive in global competition in the economic field. This Islamic boarding school can complement the curriculum with various entrepreneurial activities such as trending, farming, herding fish, herding cattle, herding goats, and cottage industries. This empowerment aims to create an entrepreneurial spirit in student through the creative economy in facing the global economy. The empowerment of students is carried out through the ABCD (Asset Base Community Development) approach with several stages including: Preparing, Discovery, Dream, Define, Design, and Destiny. As for the steps for training on entrepreneurship through the practice of making snacks, packaging, branding and selling. This training resulted in several snacks that were packaged with several packaging models according to the target market.